2010
DOI: 10.1093/heapro/daq025
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of health-promoting lifestyle behaviour in the rural areas of Hungary

Abstract: Today chronic non-communicable diseases are the major cause of death and disability worldwide. Chronic diseases are determined by common risk factors (e.g. smoking). The purpose of this study was to develop a health-promoting behaviour index, and to evaluate the impact of the social and the demographic characteristics of the individuals, self-rated health and certain features of settlements on the score of this index. A population-based, cross-sectional health survey was conducted. Altogether 91 settlements wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
1
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 16 publications
6
29
1
15
Order By: Relevance
“…Felton et al (1997) draw on a survey data and find that females have higher odds of engaging in health-enhancing lifestyle than males. Similar findings are evidenced by a more recent study by Paulik et al (2010). The authors find that Hungarian women are more likely to live a healthy lifestyle compared to men.…”
Section: Literature Reviewsupporting
confidence: 86%
“…Felton et al (1997) draw on a survey data and find that females have higher odds of engaging in health-enhancing lifestyle than males. Similar findings are evidenced by a more recent study by Paulik et al (2010). The authors find that Hungarian women are more likely to live a healthy lifestyle compared to men.…”
Section: Literature Reviewsupporting
confidence: 86%
“…This study also showed that the odds of regular smoking and alcohol consumption did not differ significant between the poorest and the richest groups. The study focused on rural areas in Hungary (Paulik et al, 2010) confirmed that material circumstance (categorised into poor, acceptable and good) has significant influence on healthy behaviour. They proved that the odds of healthy behaviour were higher for living in good material circumstances than for living in poor circumstances.…”
Section: Resultsmentioning
confidence: 78%
“…[22][23][24] Araştırmaya katılan bireylerin sağlıklı yaşam tarzı davranışları sosyo-demografik özelliklere göre incelendiğinde; kadınlar, evli olanlar, üniversite mezunları, ekonomik durumu iyi olanlar ve sağlığını iyi olarak değerlendirenler arasında sağlıklı yaşam tarzı alışkanlıklarına sahip olan daha fazla kişi olduğu belirlenmiştir. Sosyo-demografik özelliklere ilişkin bu sonuçlar Türkiye geneli istatistiklerle, [20,[35][36] Türkiye'de sağlıklı yaşam tarzı davranışlarına yöne-lik yaşlılar üzerine yapılan çalışmalarla [22][23][24][25]30] ve diğer ülkelerde yapılan çalışmalarla [8,[13][14][15][16][18][19] Daha önce yapılan çok sayıda kesitsel ve kohort çalışmada sosyo-ekonomik faktörlerin yaşlı yaşam kalitesi üzerine etkisi kanıtlanmıştır. [39][40][41][42] Bu çalışmanın temel konusu olan sağlıklı yaşam tarzı alışkanlıkları açısından yaşam kalitesi değer-lendirildiğinde; yeterli meyve-sebze tüketiminin yaşlı sağlığı ve yaşam kalitesini olumlu etkilediğini gösteren çalışmalar mevcuttur.…”
Section: Sağlıklı Yaşam Tarzı Alışkanlıklarıunclassified
“…[6,[8][9][10][11][12][13][14] Değiştirilebilir yaşam tarzı davranışları; mortalite ve kronik hastalık gibi sağlık sonuçları ile ilişkilerini gösteren epidemiyolojik çalışmalara dayanarak; fiziksel hareketsizlik, tütün kullanımı, kötü beslenme, madde kullanımı (alkol dâhil) olarak kabul edilmektedir. [6,7,10,11,[15][16][17][18][19] Dünyada her yıl en az 5,1 milyon kişi tütün kullanma, 3,2 mil-yon kişi fiziksel hareketsizlik, 2,8 milyon kişi fazla kilolu veya şişman olma ve 2,7 milyon kişi yetersiz sebze ve meyve tüketmeye bağlı sorunlar nedeniyle ölmektedir. [7,20] Kanıtlar bu faktör-lerde iyileşmelerin, ileri yaşla artan fonksiyonel sınırlamaları önleyebileceği ve böylece daha sağ-lıklı, daha aktif ve daha bağımsız yaşlanmanın sağ-lanabileceğini düşündürmektedir.…”
Section: Introductionunclassified
See 1 more Smart Citation